Territoriality as a factor associated with home advantage. A comparative study by regions in professional Spanish football and futsal leagues - J. Sampedro; J. Prieto (Asociación Española de Ciencias del Deporte, 2011)
The aim of this research was to study home advantage in the professional Spanish football and futsal leagues in a general way, and to make a regional analysis to identify geographical variations and whether they can be interpreted in terms of territoriality as a factor associated with home advantage. Last fifteen seasons were examined, after the introduction of the current system of three points for a win in 1995-96. Home advantage found in the two leagues under study was close to the worldwide figure in football. Individual analysis after controlling team ability showed no significant differences between any of the teams. The analysis of specific regions from elsewhere in the country only showed significant differences that can be interpreted in terms of territoriality in Catalonia within futsal league. Catalan teams also presented the highest values for home advantage in the football league. This suggests considering Catalonia for future work as a region likely to be studied individually in terms of territoriality. Key Words:Home advantage, territoriality, regions, football, futsal